Difference between revisions of "2023 AMC 12A Problems/Problem 20"

(Solution 1)
Line 4: Line 4:
 
==Solution 1==
 
==Solution 1==
  
First, let <math>R(n) be the sum of the </math>n<math>th row. Now, with some observations and math instinct, we can guess that </math>R(n) = 2^n - n<math>
+
First, let <math>R(n)</math> be the sum of the <math>n</math>th row. Now, with some observations and math instinct, we can guess that <math>R(n) = 2^n - n</math>
  
 
now we try to prove it by induction,
 
now we try to prove it by induction,
  
</math>R(1) = 2^n - n = 2^1 - 1 = 1<math> (works for base case!)
+
<math>R(1) = 2^n - n = 2^1 - 1 = 1</math> (works for base case)
  
</math>R(k) = 2^k - k<math>
+
<math>R(k) = 2^k - k</math>
  
</math>R(k+1) = 2^{k+1} - (k + 1) = 2(2^k) - k - 1<math>
+
<math>R(k+1) = 2^{k+1} - (k + 1) = 2(2^k) - k - 1</math>
  
Now by definition from the question, the next row is always: double the sum of last row (Each number from last row branches off toward left and right to the next row), plus # of new row, minus 2 (leftmost and rightmost are just 1)
+
Now by definition from the question, the next row is always<math>:</math> double the sum of last row (Each number from last row branches off toward left and right to the next row), plus # of new row, minus 2 (leftmost and rightmost are just 1)
  
</math>2(2^k - k) + (k + 1) - 2 = 2(2^k) - k - 1<math>
+
<math>2(2^k - k) + (k + 1) - 2 = 2(2^k) - k - 1</math>
  
 
Hence proven.
 
Hence proven.
  
Simply substitute </math>n = 2023<math>, we get </math>R(2023) = 2^2023 - 2023$
+
Simply substitute <math>n = 2023</math>, we get <math>R(2023) = 2^2023 - 2023</math>
  
 
Last digit of 2^2023 is 8, 8-3 = \boxed{\textbf{(C)} 5}
 
Last digit of 2^2023 is 8, 8-3 = \boxed{\textbf{(C)} 5}

Revision as of 22:43, 9 November 2023

Problem

Rows 1, 2, 3, 4, and 5 of a triangular array of integers are shown below.

Solution 1

First, let $R(n)$ be the sum of the $n$th row. Now, with some observations and math instinct, we can guess that $R(n) = 2^n - n$

now we try to prove it by induction,

$R(1) = 2^n - n = 2^1 - 1 = 1$ (works for base case)

$R(k) = 2^k - k$

$R(k+1) = 2^{k+1} - (k + 1) = 2(2^k) - k - 1$

Now by definition from the question, the next row is always$:$ double the sum of last row (Each number from last row branches off toward left and right to the next row), plus # of new row, minus 2 (leftmost and rightmost are just 1)

$2(2^k - k) + (k + 1) - 2 = 2(2^k) - k - 1$

Hence proven.

Simply substitute $n = 2023$, we get $R(2023) = 2^2023 - 2023$

Last digit of 2^2023 is 8, 8-3 = \boxed{\textbf{(C)} 5}

~lptoggled

See also

2023 AMC 12A (ProblemsAnswer KeyResources)
Preceded by
Problem 19
Followed by
Problem 21
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25
All AMC 12 Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png